Second life : (Sybex,John Wiley [distributor], 2007)
Second Life: The Official Guide is the perfect book for anyone interested in Linden Lab?s fascinating Second Life metaverse. This book explores in detail every aspect of Second Life?s rich and multilayered virtual world, explains how it works, and offers a wealth of information and practical advice for all Second Life residents.? The first part of the book, ?Getting a Second Life,? acquaints potential and new players with the Second Life world. It describes the metaverse?s geography as well as its society, explaining the written and unwritten rules. The second part, ?Living a Second Life,? deals with the practical and economic aspects of Second Life: creating and customizing an avatar, building objects, scripting, and making money. The third part of the book, ?Success in Second Life,? discusses ways to enjoy Second Life more. This section includes profiles of successful Second Life residents, discusses fascinating in-world events, and examines how some are using Second Life for business, training, and other purposes. The book closes with a glossary as well as quick-reference and additional-resources appendices. The accompanying CD-ROM features special animations, character templates, and textures created by Linden Lab exclusively for this book. The disc also guides new users through installation and includes a code that grants a special object their first time entering the metaverse.